Assessment of the Concentration of Advanced Glycation End Products in Traditional Chinese Foods. Issue 2 (6th May 2016) - Xu, Rui; Yue, Lu; Kang, Shimo; Liu, Ling
Abstract: Advanced glycation end products (AGEs) are common by‐products of food preparation and are associated with an increased risk of diabetes and uremia. The objective of this investigation is to determine the level of crosslinked AGEs (AGE‐fl) and N ε ‐(carboxymethyl)lysine (CML) in 24 kinds of foods consumed in China. AGE‐fl and CML contents were compared, and the effects of culinary treatments and food composition on their abundance were investigated. The results showed that the composition of the foods strongly influences the CML and AGE concentrations ( P  < 0.05), but no obvious correlation was found between the contents of AGE‐fl and CML. Along with dehydration, compared with main reactions caused by heating, oxidation effectively contributes to CML production, and the correlation coefficient between the peroxide value (POV) and the CML content is 0.86. These data can be used for improving the culinary treatment methods of foods common in the Chinese cuisine. Practical Applications: The amount of crosslinked AGEs in 24 kinds of Chinese foods and effects of culinary treatment methods and material composition were investigated. These data can be used for improving the culinary treatment methods of foods common in Chinese cuisine and other cuisines.